Does the Nose Have a Function Beyond Breathing? - DeRosa, Jaimie (Facial Plastic Surgery, 2016)
This article examines how functional nasal surgery can result in aesthetic improvement to the nose. We performed a literature search examining functional rhinoplasty with resultant aesthetic benefits. We also conducted a review of various techniques that can be used to correct functional nasal obstruction that also achieve aesthetic improvement(s).Although there are data demonstrating improvements to quality of life after functional and aesthetic nasal surgery, there is limited work linking the close relationship between functional nasal surgery with resultant aesthetic improvements.Functional rhinoplasty to correct nasal obstruction can also result in aesthetic improvements. Perhaps reconsideration of separating these closely tied issues is needed. A formal study looking at the degree of worsened, unchanged, and improved nasal aesthetics that occurs after true functional rhinoplasty, from both objective and subjective viewpoints, should be considered.
Keywords: functional rhinoplasty; aesthetic rhinoplasty; nasal grafting